IMPROVING THE CONTROL SYSTEM OF MECHATRON MODULES WITH PRESSURE TREATMENT ON METALS (Modern education and development, 2025)
This article explores advancements in the control systems of mechatron modules used for pressure treatment of metals. By integrating precision sensors, adaptive algorithms, and real-time feedback mechanisms, the proposed improvements enhance the efficiency, accuracy, and reliability of metal processing. The study includes a literature review, experimental methods, results, and discussions, culminating in conclusions and suggestions for future research.